High accuracy dual split ring resonator-defected ground structure based microwave sensor for material characterization - Misran, Mohamad Harris; Meor Said, Maizatul Alice; Othman, Mohd Azlishah; Zabri @ Suhaimi, Siti Normi; Ruslan, Eliyana; Shairi, Noor Azwan; Zakaria, Zahriladha; Babale, Suleiman Aliyu; Idris, Mohd Zahid (Islamic Azad University, 2025)
Microwave sensors have grown in popularity in recent years because of their contactless sensing capability, real-time detection capability, measurement, accuracy, ease of manufacture and robustness. They have become one of the primary choices in smart sensing applications. However, some of their key limitations, such as accuracy, sensitivity, and selectivity, might be regarded as limiting their utilization and application range. Thus, this project proposed to design and develop a high-accuracy microwave sensor for material characterization. This microwave sensor uses a Defected Ground Structure (DGS) to enhance sensor accuracy in determining the dielectric characteristics of the material under test (MUT). The sensor achieved high accuracy with a percentage error of 0.56% to 1.86% for the tested various MUTs, demonstrating reliable precision. The DGS significantly enhances performance, optimizing efficiency and compactness while reducing transmission losses on cost-effective substrates like FR4. Its high Q-factor of 595 enables detecting small dielectric constant variation